THE EFFECT OF BASIC LIFE SUPPORT HEALTH EDUCATION WITH VIDEO LEARNING METHOD ON MOTIVATION TO HELP VICTIMS - Sri Anik Rustini; Ninik Ambar Sari; Merina Widyastuti; Ceria Nurhayati; Faridah Faridah (Jurnal Keperawatan Respati Yogyakarta, 2022)
Cardiac arrest is a condition in which there is a sudden cessation of the normal circulation of blood due to failure of the heart to contract effectively during the systolic phase. Basic Life Support is an advanced life support for cardiac arrest patients which aims to stop the process leading to death. The high mortality rate due to cardiac arrest is influenced by the lack of knowledge of how to handle cardiac arrest victims so that the motivation to help victims is minimal in the community. This study aims to see the effect of Basic Life Support health education on the motivation to help victims. Pre Experimental Research Design with One-group pre-post test design. Population of level 3 students of STIKES Hang Tuah Surabaya. Sampling using simple random sampling. The number of samples is 88 people. The independent research variable is health education with the Basic Life Support learning video method, the dependent variable is motivation to help victims. The measuring instrument was given 2 times for health promotion. This study used a questionnaire and the data were analyzed using the Wilcoxon test. The results showed that the factors that influenced the level of knowledge with motivation to help p < 0.000 where, p value < 0.05, then there was an influence before being given health education and after being given Basic Life Support health education on the motivation to help victims. The implication of the research is that it is necessary to provide basic life support health education to students for first aid for cardiac arrest victims.